Geographic Information System for Freshwater Aquaculture Using Web Platform - Saumia Rahmi Putri; Asril Asril; Raimon Efendi (Komunitas Dosen Indonesia, 2025)
Freshwater aquaculture in Dharmasraya Regency plays a vital role in local food security and economic development, yet data management practices remain limited to static tabular records. This lack of spatial representation hampers effective planning, monitoring, and decision-making by the Fisheries and Food Agency. To address this issue, the present study develops a web-based Geographic Information System (GIS) tailored for freshwater aquaculture that integrates spatial visualization with comprehensive attribute data, including fish species, cultivation methods, pond size, and production outputs. The novelty of this research lies in three aspects: the integration of attribute and geospatial data into a unified platform, district-level filtering and route mapping to aquaculture sites, and the use of open-source technologies such as Leaflet.js and Chart.js to ensure interactivity, accessibility, and scalability. The system was developed using the Waterfall model, covering requirement analysis, design, implementation, and black-box testing for validation. Results show that the GIS successfully displays aquaculture distribution maps, interactive production graphs, and user-friendly data management features that align with stakeholder needs. Compared to previous GIS applications, which often emphasize coastal aquaculture or rely on satellite imagery, this system directly supports inland aquaculture management at the district level. Beyond technical contributions, the platform delivers practical benefits by enabling local authorities to monitor aquaculture spatially, improving transparency for the public, and supporting sustainable fisheries development. This study thus demonstrates how a district-level WebGIS can bridge the gap between static data and actionable decision support in aquaculture management.